Human Neural Stem Cells Overexpressing Choline Acetyltransferase Restore Unconditioned Fear in Rats with Amygdala Injury - Kyungha Shin; Yeseul Cha; Kwang Sei Kim; Ehn-Kyoung Choi; Youngjin Choi; Haiyu Guo; Young-Hwan Ban; Jong-Choon Kim; Dongsun Park; Yun-Bae Kim (Behavioural Neurology, 2016)
Amygdala is involved in the fear memory that recognizes certain environmental cues predicting threatening events. Manipulation of neurotransmission within the amygdala affects the expression of conditioned and unconditioned emotional memories such as fear freezing behaviour. We previously demonstrated that F3.ChAT human neural stem cells (NSCs) overexpressing choline acetyltransferase (ChAT) improve cognitive function of Alzheimer’s disease model rats with hippocampal or cholinergic nerve injuries by increasing acetylcholine (ACh) level. In the present study, we examined the effect of F3.ChAT cells on the deficit of unconditioned fear freezing. Rats given N-methyl-d-aspartate (NMDA) in their amygdala 2 weeks prior to cat odor exposure displayed very short resting (freezing) time compared to normal animals. NMDA induced neuronal degeneration in the amygdala, leading to a decreased ACh concentration in cerebrospinal fluid. However, intracerebroventricular transplantation of F3.ChAT cells attenuated amygdala lesions 4 weeks after transplantation. The transplanted cells were found in the NMDA-injury sites and produced ChAT protein. In addition, F3.ChAT-receiving rats recuperated freezing time staying remote from the cat odor source, according to the recovery of brain ACh concentration. The results indicate that human NSCs overexpressing ChAT may facilitate retrieval of unconditioned fear memory by increasing ACh level.